Selective Enforcement Dalam Penegakan Hukum Pencemaran Nama Baik Di Ruang Digital Antara Perkara Bibi Kelinci Dan Baiq Nuril - Farhan Hanif Nurhadi; Endik Wahyudi; Idris Wasauha (CV Edujavare Publishing, 2026)
The expansion of digital communication has transformed the way information is shared while increasing legal disputes related to online defamation. In Indonesia, the defamation provisions of the Electronic Information and Transactions Law (ITE Law) have been applied not only to defamatory expressions but also to individuals reporting alleged criminal acts or recounting personal experiences connected with the public interest. This study analyzes the application of the ITE Law in the Bibi Kelinci and Baiq Nuril cases and evaluates whether the criminalization of the aggrieved parties is compatible with the objectives of the ITE Law and the principle of victim protection. Using a normative juridical method, this research adopts statutory, conceptual, and case approaches. Legal materials were collected through library research and examined qualitatively. The analysis demonstrates differing law enforcement patterns between the two cases. Baiq Nuril, although positioned as a victim, was convicted under the ITE Law, whereas the Bibi Kelinci dispute was resolved through restorative justice. These contrasting outcomes indicate inconsistent legal enforcement and insufficient implementation of equality before the law and victim protection. Accordingly, enforcement of online defamation provisions should prioritize proportionality, contextual assessment, public interest, and legal certainty